Consensus recommendation for prenatal, neonatal and postnatal management of congenital cytomegalovirus infection from the European congenital infection initiative (ECCI) - Marianne Leruez-Ville; Christos Chatzakis; Daniele Lilleri; Daniel Blazquez-Gamero; Ana Alarcon; Nicolas Bourgon; Ina Foulon; Jacques Fourgeaud; Anna Gonce; Christine E. Jones; Paul Klapper; André Krom; et al. (Elsevier, 2024)
Summary: Congenital cytomegalovirus (cCMV) infection carries a significant burden with a 0.64% global prevalence and a 17-20% chance of serious long-term effects in children. Since the last guidelines, our understanding, particularly regarding primary maternal infections, has improved. A cCMV guidelines group was convened under the patronage of the European Society of Clinical Virology in April 2023 to refine these insights. The quality and validity of selected studies were assessed for potential biases and the GRADE framework was employed to evaluate quality of evidence across key domains. The resulting recommendations address managing cCMV, spanning prevention to postnatal care. Emphasizing early and accurate maternal diagnosis through serological tests enhances risk management and prevention strategies, including using valaciclovir to prevent vertical transmission. The guidelines also strive to refine personalized postnatal care based on risk assessments, ensuring targeted interventions for affected families.